A method for preparing and performance regulating of high strength and toughness CrNiCN thin film on surface of thin-wall substrate
Patent Information
- Application Number
- CN202410604950.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-15
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2044-05-15
AI Technical Summary
[0006]然而,现有CrCN涂层沉积技术通常是针对结构件而实施的,并不适用于在薄壁(壁厚不大于1mm)基体上沉积CrNiCN薄膜
[0015]Beneficial Effects: This invention, by incorporating specific Ni into the coating, achieves a CrNiCN coating thickness of 4.0–4.5 μm. This not only improves the coating's density, reduces columnar defects and pores, and enhances its toughness, but also provides advantages such as high hardness and high wear resistance. The coating prepared using multi-arc ion plating technology exhibits good density, high hardness, good wear resistance, and excellent film-substrate adhesion. The coating obtained by this invention has a uniform elemental distribution without element aggregation, resulting in good mechanical properties and abrasion resistance. The entire coating process is stable and safe. Most importantly, it significantly reduces the number of large molten droplets ejected at the moment the target is activated, reducing large particles in the film and ensuring the production of high-quality films. Crucially, this invention effectively avoids the formation of numerous grooves on the surface of the CrNiCN film on a thin-walled stainless steel substrate. The sputtered CrNi ions gain kinetic energy and accelerate towards the substrate, bombarding it. This process removes loosely bonded atoms from the substrate surface, leaving behind tightly bonded, defect-free film atoms, thus improving film quality. In addition, the bias voltage will also attract some argon ions. The bombardment of argon ions can clean the impurities on the substrate surface, which is also beneficial to improving the film quality.
Smart Images

Figure CN118547250B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of CrCN coating preparation technology, specifically relating to a method for preparing and controlling the performance of high-strength and high-toughness CrNiCN thin films on thin-walled substrates. Background Technology
[0002] In the marine environment, marine engineering equipment materials are subject to the interaction of wear and corrosion. Wear exacerbates the erosion by corrosive media, and the erosion by corrosive media, in turn, reduces the wear resistance of materials, further intensifying wear, thus forming a synergistic damage phenomenon of wear and electrochemical corrosion. Therefore, the design of coating materials with comprehensive wear and corrosion resistance is an urgent need for the development of high-end marine equipment and a research hotspot in recent years.
[0003] Depositing transition metal nitride coatings on material surfaces via physical / chemical vapor deposition (PVD / CVD) is a common method for optimizing material properties. Currently, chromium nitride (CrN) is considered the most promising marine protective coating. However, the high coefficient of friction of CrN coatings limits their application under some harsh operating conditions, and CrN coatings typically grow in a continuous columnar manner during deposition, resulting in numerous pinholes and microcracks, which reduce their density and service life.
[0004] Elemental doping is one of the most effective methods to optimize the microstructure and improve the overall performance of materials. Recent studies have shown that doping CrN coatings with elements such as Al, Si, and C can significantly improve the mechanical properties of the coating and reduce its coefficient of friction. Zhang et al. deposited CrCN coatings on different substrates using multi-arc ion plating technology and pointed out that the tribocorrosion behavior of the coating is closely related to its substrate. The results show that the CrCN coating has the best tribocorrosion performance in artificial seawater; however, the CrCN coating exhibits increased brittleness due to its high hardness, which easily leads to crack initiation.
[0005] The study also showed that incorporating alloying elements (such as Ni) into TiN coatings may help to further improve performance. For example, TiNiN-based coatings manufactured by physical vapor deposition (PVD) technology have been found to improve the mechanical properties of engineered parts because they have higher hardness and elastic modulus, as well as enhanced toughness and improved thermal stability.
[0006] However, existing CrCN coating deposition technologies are typically implemented for structural components and are not suitable for depositing CrNiCN films on thin-walled substrates (wall thickness no greater than 1 mm). More importantly, because depositing CrNiCN films on thin-walled substrates requires bombardment and high-temperature environments, it easily leads to numerous ploughing grooves on the CrNiCN film surface, severely affecting its uniformity, wear resistance, and stability. Summary of the Invention
[0007] In order to solve the technical problems mentioned in the background art, the present invention aims to provide a method for preparing and controlling the performance of high-strength and high-toughness CrNiCN thin films on thin-walled substrates.
[0008] The present invention adopts the following technical solution.
[0009] A method for preparing CrNiCN thin films on a thin-walled substrate, comprising the following steps: Step 1: Pre-treat the surface of the thin-walled substrate and install the thin-walled substrate on the substrate mounting bracket; Step 2: Deposit a Cr50Ni50CN coating on the surface of the thin-walled substrate.
[0010] Further, step 2 includes: The target material is Ni50Cr50wt.%, and the coating equipment is a process arc ion plating equipment with a 300mm long electromagnetic coil. The thin-walled substrate, after grinding and polishing, was ultrasonically cleaned in anhydrous ethanol, dried, and placed on a mounting bracket with the substrate facing the target surface. The coating temperature was controlled at 300℃, and the vacuum was reduced to 5.6*10. -3 After Pa, perform ion etching for 50 minutes; Then argon gas is introduced, the gas pressure is controlled at 1.0 Pa, the target is turned on, the arc current is controlled at 100 A, the coil current is set at 0.5 A, the thin-walled substrate bias voltage is -100 V*60%, and the transition layer is deposited for 10 minutes. Then nitrogen gas was introduced, the pressure was adjusted to 1.5 Pa, and the nitride layer was deposited for 5 minutes; Then C2H2 is introduced, C2H2 / (C2H2+N2)=15%, the gas pressure is controlled at 1.5Pa, the bias voltage starts from -100V*60% and increases to -10V / 5min, and the deposition takes 90 minutes in total; the etching source is turned on at 60 minutes, ion beam assisted deposition takes 30 minutes, and the furnace is stopped at 150 degrees.
[0011] Further, step 1 includes: mechanically grinding the stainless steel thin-walled substrate with SiC sandpaper, followed by mirror polishing, and then ultrasonically cleaning the treated 316L thin-walled substrate in deionized water, acetone solution and anhydrous ethanol solution for 15 minutes in sequence, and drying it after cleaning for use.
[0012] As a preferred embodiment, the wall thickness of the thin-walled substrate is no greater than 0.7 mm.
[0013] To effectively prevent the formation of numerous furrows on the surface of the CrNiCN thin film, the substrate mounting bracket is made of a stainless steel plate with negative pressure adsorption holes. The diameter of the negative pressure adsorption holes is no greater than 3 mm, the spacing between adjacent negative pressure adsorption holes is no greater than 10 mm, and the surface roughness of the stainless steel plate is no greater than Ra0.8a. The negative pressure adsorption holes are connected to a vacuum adsorption system, and the thin-walled substrate is laid flat on the surface of the stainless steel plate and adsorbed.
[0014] A method for regulating the properties of high-strength and high-toughness CrNiCN thin films on thin-walled substrates, comprising the following steps: Step 11: Mechanically grind the stainless steel thin-walled substrate with SiC sandpaper, followed by mirror polishing. Place the treated 316L thin-walled substrate in deionized water, acetone solution, and anhydrous ethanol solution for ultrasonic cleaning for 15 minutes in sequence. After cleaning, dry it for use and install the thin-walled substrate on the substrate mounting bracket. The wall thickness of the thin-walled substrate is 0.4-0.5 mm. Step 12: The target material is Ni50Cr50wt.%, and the coating equipment is a process arc ion plating equipment with a 300mm long electromagnetic coil. The thin-walled substrate, after grinding and polishing, was ultrasonically cleaned in anhydrous ethanol, dried, and placed on a mounting bracket with the substrate facing the target surface. The coating temperature was controlled at 300℃, and the vacuum was reduced to 5.6*10. -3 After Pa, perform ion etching for 50 minutes; Then argon gas is introduced, the gas pressure is controlled at 1.0 Pa, the target is turned on, the arc current is controlled at 100 A, the coil current is set at 0.5 A, the thin-walled substrate bias voltage is -100 V*60%, and the transition layer is deposited for 10 minutes. Then nitrogen gas was introduced, the pressure was adjusted to 1.5 Pa, and the nitride layer was deposited for 5 minutes; Then C2H2 is introduced, C2H2 / (C2H2+N2)=15%, the gas pressure is controlled at 1.5Pa, the bias voltage starts from -100V*60% and increases to -10V / 5min, and the deposition takes 90 minutes in total; the etching source is turned on at 60 minutes, ion beam assisted deposition takes 30 minutes, and the furnace is stopped at 150 degrees. Step 13: Vacuum annealing is performed on the thin-walled substrate with the deposited Cr50Ni50CN coating. After heating to 600℃, the temperature is held for one hour and then cooled in the furnace.
[0015] Beneficial Effects: This invention, by incorporating specific Ni into the coating, achieves a CrNiCN coating thickness of 4.0–4.5 μm. This not only improves the coating's density, reduces columnar defects and pores, and enhances its toughness, but also provides advantages such as high hardness and high wear resistance. The coating prepared using multi-arc ion plating technology exhibits good density, high hardness, good wear resistance, and excellent film-substrate adhesion. The coating obtained by this invention has a uniform elemental distribution without element aggregation, resulting in good mechanical properties and abrasion resistance. The entire coating process is stable and safe. Most importantly, it significantly reduces the number of large molten droplets ejected at the moment the target is activated, reducing large particles in the film and ensuring the production of high-quality films. Crucially, this invention effectively avoids the formation of numerous grooves on the surface of the CrNiCN film on a thin-walled stainless steel substrate. The sputtered CrNi ions gain kinetic energy and accelerate towards the substrate, bombarding it. This process removes loosely bonded atoms from the substrate surface, leaving behind tightly bonded, defect-free film atoms, thus improving film quality. In addition, the bias voltage will also attract some argon ions. The bombardment of argon ions can clean the impurities on the substrate surface, which is also beneficial to improving the film quality. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the multi-arc ion plating equipment used in the embodiment. In the figure, 1—cathode arc source, 2, 3—air inlet, 4—vacuum system, 5—substrate, 6—bias power supply; Figure 2 The friction coefficients are those in Example 1 and the comparative example; Figure 3 These are microscopic wear marks from Example 1 and the comparative example; Figure 4 This is a TEM cross-sectional image of the sample in Example 2; Figure 5 The friction coefficient and cross-sectional morphology of the sample in Example 2; Figure 6 This is a microscopic and magnified image of the wear marks on the sample in Example 2. Detailed Implementation
[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] Combination Figure 1As shown, a multi-arc ion plating equipment is used to deposit a Cr50Ni50CN coating. The multi-arc ion plating technology involves igniting an arc and moving the arc towards the cathode target under the action of a magnetic field. This causes the cathode target to act as an evaporation source, ionizing gas molecules and igniting the arc source, generating a glow discharge phenomenon to form a high-density plasma. The ionized metal positive ions enter the plasma region and collide with the reactive gas molecules and electrons. The ionized positive ions move towards the workpiece surface under the action of the electric field and are finally deposited on the workpiece surface to form a film layer. Example 1
[0019] A method for preparing CrNiCN thin films on a thin-walled substrate, comprising the following steps: Step 1: Pre-treat the surface of the thin-walled substrate and install the thin-walled substrate on the substrate mounting bracket; Specifically: The stainless steel thin-walled substrate (with a wall thickness of 0.7 mm) was mechanically polished using SiC sandpaper, followed by mirror polishing. The treated 316L thin-walled substrate was then placed in deionized water, acetone solution, and anhydrous ethanol solution for ultrasonic cleaning for 15 minutes in sequence, and then dried before use. Then, the cleaned stainless steel thin-walled substrate is mounted on a stainless steel plate with negative pressure adsorption holes. The diameter of the negative pressure adsorption holes is 2.5 mm, the spacing between adjacent negative pressure adsorption holes is 8 mm, and the surface roughness of the stainless steel plate is no greater than Ra0.8a. The negative pressure adsorption holes are connected to a vacuum adsorption system, and the thin-walled substrate is laid flat on the surface of the stainless steel plate and adsorbed. Step 2: Deposit a Cr50Ni50CN coating on the surface of the thin-walled substrate; specifically: The target material is Ni50Cr50wt.%, and the coating equipment is a process arc ion plating equipment with a 300mm long electromagnetic coil. The thin-walled substrate, after grinding and polishing, was ultrasonically cleaned in anhydrous ethanol, dried, and placed on a mounting bracket with the substrate facing the target surface. The coating temperature was controlled at 300℃, and the vacuum was reduced to 5.6*10. -3 After Pa, perform ion etching for 50 minutes; Then argon gas is introduced, the gas pressure is controlled at 1.0 Pa, the target is turned on, the arc current is controlled at 100 A, the coil current is set at 0.5 A, the thin-walled substrate bias voltage is -100 V*60%, and the transition layer is deposited for 10 minutes. Then nitrogen gas was introduced, the pressure was adjusted to 1.5 Pa, and the nitride layer was deposited for 5 minutes; Then C2H2 is introduced, C2H2 / (C2H2+N2)=15%, the gas pressure is controlled at 1.5Pa, the bias voltage starts from -100V*60% and increases to -10V / 5min, and the deposition takes 90 minutes in total; the etching source is turned on at 60 minutes, ion beam assisted deposition takes 30 minutes, and the furnace is stopped at 150 degrees. The final Cr50Ni50CN coating thickness was 4.0–4.5 μm, and the friction coefficient was 0.36 after a 60-minute friction test. Comparative Example 1
[0020] A method for preparing CrNiCN thin films on a thin-walled substrate, comprising the following steps: Step 1: Pre-treat the surface of the thin-walled substrate and install the thin-walled substrate on the substrate mounting bracket; Specifically: The stainless steel thin-walled substrate (with a wall thickness of 0.7 mm) was mechanically polished using SiC sandpaper, followed by mirror polishing. The treated 316L thin-walled substrate was then placed in deionized water, acetone solution, and anhydrous ethanol solution for ultrasonic cleaning for 15 minutes in sequence, and then dried before use. Then, press the cleaned stainless steel thin-walled substrate edges firmly onto the stainless steel plate; Step 2: Deposit a Cr20Ni80CN coating on the surface of the thin-walled substrate; specifically: The target material is Ni80Cr20wt.%, and the coating equipment is a process arc ion plating equipment with a 300mm long electromagnetic coil. The thin-walled substrate, after grinding and polishing, was ultrasonically cleaned in anhydrous ethanol, dried, and placed on a mounting bracket with the substrate facing the target surface. The coating temperature was controlled at 300℃, and the vacuum was reduced to 5.6*10. -3 After Pa, perform ion etching for 50 minutes; Then argon gas is introduced, the gas pressure is controlled at 1.0 Pa, the target is turned on, the arc current is controlled at 100 A, the coil current is set at 0.5 A, the thin-walled substrate bias voltage is -100 V*60%, and the transition layer is deposited for 10 minutes. Then nitrogen gas was introduced, the pressure was adjusted to 1.5 Pa, and the nitride layer was deposited for 5 minutes; Then C2H2 is introduced, C2H2 / (C2H2+N2)=15%, the gas pressure is controlled at 1.5Pa, the bias voltage starts from -100V*60% and increases to -10V / 5min, and the deposition takes 90 minutes in total; the etching source is turned on at 60 minutes, ion beam assisted deposition takes 30 minutes, and the furnace is stopped at 150 degrees. The final Cr20Ni80CN coating thickness was 4.0–4.5 μm, and the friction coefficient was 0.38 after a 60-minute friction test. Comparative Example 2
[0021] A method for preparing CrCN thin films on a thin-walled substrate, comprising the following steps: Step 1: Pre-treat the surface of the thin-walled substrate and install the thin-walled substrate on the substrate mounting bracket; Specifically: The stainless steel thin-walled substrate (with a wall thickness of 0.7 mm) was mechanically polished using SiC sandpaper, followed by mirror polishing. The treated 316L thin-walled substrate was then placed in deionized water, acetone solution, and anhydrous ethanol solution for ultrasonic cleaning for 15 minutes in sequence, and then dried before use. Then, press the cleaned stainless steel thin-walled substrate edges firmly onto the stainless steel plate; Step 2: Deposit a CrCN coating on the surface of the thin-walled substrate; specifically: Cr target material is selected, and the coating equipment adopts process arc ion plating equipment with a 300mm long electromagnetic coil; The thin-walled substrate, after grinding and polishing, was ultrasonically cleaned in anhydrous ethanol, dried, and placed on a mounting bracket with the substrate facing the target surface. The coating temperature was controlled at 300℃, and the vacuum was reduced to 5.6*10. -3 After Pa, perform ion etching for 50 minutes; Then argon gas is introduced, the gas pressure is controlled at 1.0 Pa, the target is turned on, the arc current is controlled at 100 A, the coil current is set at 0.5 A, the thin-walled substrate bias voltage is -100 V*60%, and the transition layer is deposited for 10 minutes. Then nitrogen gas was introduced, the pressure was adjusted to 1.5 Pa, and the nitride layer was deposited for 5 minutes; Then C2H2 is introduced, C2H2 / (C2H2+N2)=15%, the gas pressure is controlled at 1.5Pa, the bias voltage starts from -100V*60% and increases to -10V / 5min, and the deposition takes 90 minutes in total; the etching source is turned on at 60 minutes, ion beam assisted deposition takes 30 minutes, and the furnace is stopped at 150 degrees. The final CrCN coating thickness was 4.0–4.5 μm, and the friction coefficient was 0.4 after a 60-minute friction test.
[0022] like Figure 2 As shown, the friction curves correspond to the CrCN coating, Cr50Ni50CN coating, and Cr20Ni80CN coating, respectively. An MST-3000 friction and wear testing machine was used, employing Si3N4 grinding balls, with a load of 9N, a friction radius of 5mm, a rotation speed of 500r / min, and a friction time of 60min, to obtain the average friction coefficient and its variation curve. The average friction coefficients of the CrCN coating, Cr50Ni50CN coating, and Cr20Ni80CN coating are 0.40, 0.36, and 0.38, respectively. This indicates that adding Ni to the CrCN coating can effectively reduce the coating's friction coefficient. With the addition of Ni, the friction coefficient first decreases and then increases, reaching its best performance when the Ni content reaches 50%. The Cr50Ni50CN coating exhibits the best wear resistance.
[0023] like Figure 3The images show microscopic and magnified views of the wear tracks. Figures a, b, and c show that the wear tracks of sample S1 (the sample in Comparative Example 2) show gaps, which is verified in subsequent magnified views; numerous cracks appear on the coating surface. Sample S2 (the sample in Example 1) has a smooth surface with no obvious cracks. Figure h shows that the coating surface of sample S3 (the sample in Comparative Example 1) shows numerous shallow furrows, and Figure i indicates shallow cracks in the coating. It is evident that the Cr50Ni50CN coating exhibits the best wear resistance. When the Ni content in the CrNiCN coating is low, Ni dissolves in the CrCN lattice, resulting in solid solution strengthening. Simultaneously, increasing the Ni content in the CrNiCN coating improves the coating's density, reduces columnar structural defects and pores, thus simultaneously improving the coating's hardness and toughness. Through friction coefficient and wear track surface analysis, the CrNiCN film exhibits the best wear resistance and highest strength when the Ni content reaches 50%.
[0024] The scheme described in Example 1 effectively avoids the formation of numerous grooves on the surface of the CrNiCN film on the stainless steel thin-walled substrate. The sputtered CrNi ions gain kinetic energy and accelerate towards the substrate, bombarding it. This process removes loosely bonded atoms from the substrate surface, leaving behind tightly bonded, defect-free film atoms, thus improving film quality. Furthermore, the bias voltage attracts some argon ions, whose bombardment can clean impurities on the substrate surface, further contributing to improved film quality. Example 2
[0025] The sample obtained in Example 1 was subjected to vacuum annealing (heated to 600°C, held for one hour, and then cooled in the furnace), and the results are as follows. Figure 4 As shown, the TEM cross-section reveals that the Cr50Ni50CN coating and the substrate formed a satisfactory interface. The presence of the Cr50Ni50CN coating and the substrate can also be clearly observed in the TEM cross-sectional image, indicating that no obvious interdiffusion behavior occurred between the coating and the substrate after annealing. A tightly packed crystalline structure appeared in the coating, and the diameter of the crystal blocks was between 40nm and 80nm. It can be clearly seen that the solid solution state of Cr and Ni was broken, forming a fine crystalline structure.
[0026] Friction, wear, and abrasion resistance tests were performed on the vacuum-annealed samples, and the results are as follows: Figure 5 and Figure 6 As shown. Figure 5 The friction coefficient and cross-sectional morphology of the sample in this embodiment are shown. The average friction coefficient is 0.42, the wear track depth is 0.7 μm, and the wear rate is calculated to be 1.39 × 10⁻⁶ using the formula. -6 mm 3 / N·m, the wear resistance of the coating increased by nearly 4 times after annealing. Figure 6The images shown are microscopic and magnified views of the wear marks on the sample in this embodiment. Only slight polishing wear occurred on the coating surface. The macroscopic image shows a small amount of grinding at the edge of the wear marks. In the magnified view, it is shown that the particles on the coating surface were ground off, while the coating as a whole did not experience severe wear. After vacuum annealing at 600°C, the coating obtained a dense structure, which prevented the occurrence of dislocations and slip, thereby improving the wear resistance of the coating. Example 3
[0027] A method for regulating the properties of high-strength and high-toughness CrNiCN thin films on thin-walled substrates, comprising the following steps: Step 11: Mechanically grind the stainless steel thin-walled substrate using SiC sandpaper, followed by mirror polishing. Then, sequentially immerse the treated 316L thin-walled substrate in deionized water, acetone solution, and anhydrous ethanol solution for ultrasonic cleaning for 15 minutes each. After cleaning, dry the substrate before use and install it on a substrate mounting bracket. The wall thickness of the thin-walled substrate is 0.5 mm. Step 12: The target material is Ni50Cr50wt.%, and the coating equipment is a process arc ion plating equipment with a 300mm long electromagnetic coil. The thin-walled substrate, after grinding and polishing, was ultrasonically cleaned in anhydrous ethanol, dried, and placed on a mounting bracket with the substrate facing the target surface. The coating temperature was controlled at 300℃, and the vacuum was reduced to 5.6*10. -3 After Pa, perform ion etching for 50 minutes; Then argon gas is introduced, the gas pressure is controlled at 1.0 Pa, the target is turned on, the arc current is controlled at 100 A, the coil current is set at 0.5 A, the thin-walled substrate bias voltage is -100 V*60%, and the transition layer is deposited for 10 minutes. Then nitrogen gas was introduced, the pressure was adjusted to 1.5 Pa, and the nitride layer was deposited for 5 minutes; Then C2H2 is introduced, C2H2 / (C2H2+N2)=15%, the gas pressure is controlled at 1.5Pa, the bias voltage starts from -100V*60% and increases to -10V / 5min, and the deposition takes 90 minutes in total; the etching source is turned on at 60 minutes, ion beam assisted deposition takes 30 minutes, and the furnace is stopped at 150 degrees. Step 13: Vacuum annealing is performed on the thin-walled substrate with the deposited Cr50Ni50CN coating. After heating to 600℃, the temperature is held for one hour and then cooled in the furnace.
Claims
1. A method for preparing a high-strength and tough CrNiCN thin film on a thin-walled substrate, characterized in that the steps include... include: Step 1: Pre-treat the surface of the thin-walled substrate and install the thin-walled substrate on the substrate mounting bracket; Step 2: Deposit a Cr50Ni50CN coating on the surface of a thin-walled substrate; Step 2 includes: The target material is Ni50Cr50wt.%, and the coating equipment is a process arc ion plating equipment with a 300mm long electromagnetic coil. The thin-walled substrate, after grinding and polishing, was ultrasonically cleaned in anhydrous ethanol, dried, and placed on a mounting bracket with the substrate facing the target surface. The coating temperature was controlled at 300℃, and the vacuum was reduced to 5.6*10. -3 After Pa, perform ion etching for 50 minutes; Then argon gas is introduced, the gas pressure is controlled at 1.0 Pa, the target is turned on, the arc current is controlled at 100 A, the coil current is set at 0.5 A, the thin-walled substrate bias voltage is -100 V*60%, and the transition layer is deposited for 10 minutes. Then nitrogen gas was introduced, the pressure was adjusted to 1.5 Pa, and the nitride layer was deposited for 5 minutes; Then C2H2 is introduced, C2H2 / (C2H2+N2)=15%, the gas pressure is controlled at 1.5Pa, the bias voltage starts from -100V*60% and increases to -10V / 5min, and the deposition takes 90 minutes in total; the etching source is turned on at 60 minutes, ion beam assisted deposition takes 30 minutes, and the furnace is stopped at 150 degrees. After step 2, the thin-walled substrate with the deposited Cr50Ni50CN coating is subjected to vacuum annealing. After heating to 600℃, it is held at that temperature for one hour and then cooled in the furnace.
2. The method for preparing high-strength and tough CrNiCN thin films on thin-walled substrates according to claim 1, characterized in that, Step 1 includes: mechanically grinding the stainless steel thin-walled substrate with SiC sandpaper, followed by mirror polishing, and then ultrasonically cleaning the treated 316L thin-walled substrate in deionized water, acetone solution and anhydrous ethanol solution for 15 minutes in sequence, and drying it after cleaning before use.
3. The method for preparing high-strength and tough CrNiCN thin films on thin-walled substrates according to claim 1 or 2, characterized in that: The wall thickness of the thin-walled substrate is no more than 0.7 mm.
4. The method for preparing high-strength and tough CrNiCN thin films on thin-walled substrates according to claim 3, characterized in that: The substrate mounting frame is made of stainless steel plate with negative pressure adsorption holes. The diameter of the negative pressure adsorption holes is no greater than 3mm, the spacing between adjacent negative pressure adsorption holes is no greater than 10mm, and the surface roughness of the stainless steel plate is no greater than Ra0.8a. The negative pressure adsorption holes are connected to a vacuum adsorption system, and the thin-walled substrate is laid flat on the surface of the stainless steel plate and adsorbed.
5. A method for regulating the properties of high-strength and high-toughness CrNiCN thin films on thin-walled substrates, characterized by the following steps: include: Step 11: Mechanically grind the stainless steel thin-walled substrate with SiC sandpaper, followed by mirror polishing. Place the treated 316L thin-walled substrate in deionized water, acetone solution, and anhydrous ethanol solution in sequence for ultrasonic cleaning for 15 minutes. After cleaning, dry it for use and install the thin-walled substrate on the substrate mounting bracket. The wall thickness of the thin-walled substrate is 0.4~0.5mm. Step 12: The target material is Ni50Cr50wt.%, and the coating equipment is a process arc ion plating equipment with a 300mm long electromagnetic coil. The thin-walled substrate, after grinding and polishing, was ultrasonically cleaned in anhydrous ethanol, dried, and placed on a mounting bracket with the substrate facing the target surface. The coating temperature was controlled at 300℃, and the vacuum was reduced to 5.6*10. -3 After Pa, perform ion etching for 50 minutes; Then argon gas is introduced, the gas pressure is controlled at 1.0 Pa, the target is turned on, the arc current is controlled at 100 A, the coil current is set at 0.5 A, the thin-walled substrate bias voltage is -100 V*60%, and the transition layer is deposited for 10 minutes. Then nitrogen gas was introduced, the pressure was adjusted to 1.5 Pa, and the nitride layer was deposited for 5 minutes; Then C2H2 is introduced, C2H2 / (C2H2+N2)=15%, the gas pressure is controlled at 1.5Pa, the bias voltage starts from -100V*60% and increases to -10V / 5min, and the deposition takes 90 minutes in total; the etching source is turned on at 60 minutes, ion beam assisted deposition takes 30 minutes, and the furnace is stopped at 150 degrees. Step 13: Vacuum annealing is performed on the thin-walled substrate with the deposited Cr50Ni50CN coating. After heating to 600℃, the temperature is held for one hour and then cooled in the furnace.
Citation Information
Patent Citations
Metallic carbide / adamantine (MeC / DLC) nanometer multi-layer film material and method for preparing the same
CN101081557A
Ni-CrSiN abrasion-resisting and corrosion-resisting coating and preparing method thereof
CN109778119A
Antibacterial antifouling metal film pad
CN110920164A
Multilayer ultra-low stress hard film with alternated layer-columnar microstructures and preparation method of multilayer ultra-low stress hard film
CN115198229A
Positioning device
CN209614603U